Predictive Factors of Mental Health in Survivors of Intimate Partner Violence in Chile - Labra-Valerdi, Paloma (Journal of interpersonal violence, 2022)
Studies about violence against women specific to the Chilean population are scarce. As a result, government treatment programs lack a local perspective. Predictor variables were analyzed in the mental health of Chilean women who have survived intimate partner abuse. Two hundred and two women who made regular visits to public Women?s Centers participated in the study; on average, they had survived 11 years of abuse. Logistic regression analyses were conducted to determine what variable/s in the history of violence best predicted the mental health variables. Among other protective factors, an increase in both resilience and the time since the last violent episode yielded a reduction in levels of general psychological distress (B = ?1.836, p < .001 and B = 1.117, p < .001 respectively), post-traumatic stress disorder (B = ?1.243, p = .002 and B = 1.221, p < .001 respectively), and depression (B = ?1.822, p < .001 and B = 1.433, p < .001 respectively). The study also noted risk factors such as a high level of additional stressors, which in turn led to increased levels of general psychological distress (B = 1.007, p = .005), post-traumatic stress disorder (B = 0.928, p = .013), and depression (B = 1.061, p = .016). The Women?s Center is the place where women feel most supported. To improve the effectiveness of treatments at these centers and aid in the recovery of women who have suffered from intimate partner violence, the predictive factors significantly related to mental health should be taken into account. This means prioritizing cases where the last episode of violence was more recent, addressing additional stressors, and promoting resilience.